The integrated working conditions and labor safety assessment in foundries - A. M. Lazarenkov; Yu. A. Nikalaichyk (Литьë и металлургия)
The results of research on working conditions and labor safety assessment in foundries are presented. The production factors of working conditions in foundries with different types of production and their impact on injuries and professional incidence of workers are considered. Recommendations to improve working conditions and reduce their impact on foundry workers are given.